A Rare Case of Pulmonary Artery Sling and Complete Atrioventricular Canal Defect in an Infant With Trisomy 21. (July 2014) - Alsaied, Tarek; Sticka, Joshua; Unaka, Ndidi; Cooper, David S.; Manning, Peter B.
Pulmonary artery sling is a very rare congenital vascular anomaly. Patients usually present in infancy with symptoms of airway compression. Patients with trisomy 21 often have upper airway obstruction, most commonly related to pharyngeal causes or subglottic stenosis. Although the incidence of congenital heart defects in patients with trisomy 21 is very high, a review of the literature showed only one previously reported case of pulmonary artery sling in an infant with trisomy 21. We report a case of pulmonary artery sling and complete atrioventricular canal defect in a one-month-old female with trisomy 21. Echocardiography is an important diagnostic method for pulmonary artery sling, but this anomaly may be easily overlooked in the presence of more commonly anticipated defects in this population.